The Effect of Folk Music Education on The Social and Personal Development of Students: A Case Study on Turkish Students Living Abroad - Özer, Levent; Özdek, Attila (Journal of History Culture and Art Research, 2021)
It has been demonstrated by various researchers that music and music education not only contribute to the social and personal development of individuals but also have many positive effects on both physical and emotional development. Besides, it is known that the negative effects of adolescence to be reduced through music and music education and that individuals studying music and/or instruments can cope well with this ups-and-downs period. Through a music education that includes multifaceted acquisition goals for individuals during adolescence, it is believed that contributions can be made in various areas. This study, which was carried out in Bishkek, Kyrgyzstan, aims to determine the social and personal gain of adolescent students living abroad and the extent that they can contribute themselves dealing with the stress and difficulties through instrument education and teaching folk song. In this research, where descriptive and qualitative approaches are at the forefront, to determine the pre/post study status of students in their social and personal development “Program Effects Case Study” and “Critical Event case study” methods and techniques have been preferred. The sample of the study, who were in early adolescence, consisted of 7th and 8th class students. For the study, a special 15-week 30-hour instrument teaching lesson plan and a repertoire of folk music melodies have been prepared. Classes were held in three groups with a total of nine students. To determine the effects of the study on students, interviews were conducted with the help of forms consisting of open-ended questions about the students’ pre/post-study status with themselves and their social environment. In the light of these findings, it was observed that there were advances in the social and personal development of students and the negative effects of early adolescence were decreased.